Applied calculus - S.T. Tan (PWS-KENT Pub. Co., 2005)
This text helps you succeed in applied calculus by using clear explanations, real-life examples, and up-to-date technology. Real-life applications-such as satellite radio subscriptions, Google's revenue, job outsourcing, and the effects of smoking bans-are drawn from the areas of business and the behavioral, life, and social sciences. Portfolio profiles give you a firsthand look at how real-world professionals use applied calculus in their work. You can also take advantage of extensive online support to enhance your learning, including video instruction and interactive tutorials that walk you step by step through examples and problems in the text